2021
DOI: 10.1021/acs.iecr.1c00293
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Mesoporous Nanoreactors with Encaged PtSn Alloy Nanoparticles for Selective Hydrogenation of Furfural to Furfuryl Alcohol

Abstract: Hollow mesoporous nanoreactors with encaged functional nanoparticles are promising heterogeneous catalysts due to the advantages related to their hollow cavities. In this study, we employ metal ion-bound polymer micelles to synthesize PtSn alloy nanoparticle-encaged hollow mesoporous nanoreactors (PtSn@HMSNs), which contain ∼4 nm PtSn alloy NPs located in ∼13 nm hollow cavities and relatively large (∼9 nm) mesoporous channels in silica shells. Relative to monometallic Pt@HMSNs and supported Pt 1 Sn 0.3 /SiO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…The selective hydrogenation of the CO over CC in the furan ring is challenging. The latter is thermodynamically favorable, leading to unwanted side reactions and low selectivity . Heterogeneous and homogeneous catalysts based on several transition metals like Ni, Pt, and Pd, ,, and Ru and Rh-based water-soluble complexes, , have been well studied in pursuit of alternatives to Cu–Cr catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The selective hydrogenation of the CO over CC in the furan ring is challenging. The latter is thermodynamically favorable, leading to unwanted side reactions and low selectivity . Heterogeneous and homogeneous catalysts based on several transition metals like Ni, Pt, and Pd, ,, and Ru and Rh-based water-soluble complexes, , have been well studied in pursuit of alternatives to Cu–Cr catalysts.…”
Section: Introductionmentioning
confidence: 99%
“… 87,88 Halilu et al synthesized low-cost, recyclable Fe(NiFe)O 4 –SiO 2 for the hydrogenation of furfural, which resulted in 93% FOL yield in heptane solvent. 89 In addition, some durable, efficient catalysts such as Cu–Fe oxides, 95 Ni–Fe alloys, 96,97 and PtSn alloy 94 have also been employed in the hydrogenation of furfural to produce FOL in recent years. It is highly desirable to design and develop cheap, robust, efficient catalysts for the hydrogenation of furfural, but noble metal catalysts should not be the first choice because they are expensive and increasingly exhausted.…”
Section: Catalytic Conversion Of Furfural Into Value-added Chemicalsmentioning
confidence: 99%
“…For example, Wu et al (2021) reported that PtNi hollow nanoframes could catalyze the FF hydrogenation with 99% yield of FFA in isopropanol within 12 h at 373 K under 2 MPa H 2 . Xiao et al (2021) reported that Pt 1 Sn 0.3 @HMSNs could yield 97% FFA in isopropanol within 5 h at 373 K under 1 MPa H 2 . However, these efficient catalytic systems need organic solvents as reaction medium, causing harm to environment, and limiting the hydrogenation application.…”
Section: Catalytic Hydrogenation Of Furfural and 5-hydroxymethylfurfuralmentioning
confidence: 99%
“…However, monometallic catalyst with relatively high metal loading always accompanied with low metal dispersion, consequently resulting in the slow reaction rate, high reaction temperature and poor selectivity to FFA/DHMF. In order to improve the catalytic performance of monometallic catalysts, the bimetallic nanoalloys have been widely studied and attracted more attention in the last decades (Fang et al, 2018;Xie et al, 2020;Xiao et al, 2021). The bimetallic nanoalloys are significantly different from the two bulk metals and take on intrinsic features, including tunable components and ratios, variable constructions, reconfigurable electronic structures, and optimizable performances.…”
Section: Introductionmentioning
confidence: 99%